Mímesis e didáxis: uma investigação acerca da poesia didática em Hesíodo e Lucrécio - Aguiar, Saulo Santana de (2022)
This research aims to study the configuration of the didactic genre as presented in two singular works of this tradition, the poems Works and Days, by Hesiod, and the On the nature of things (De rerum natura), by Lucretius, having as a guide for this investigation the concept of mimesis, which defines the act of literary creation, as advocated in the classical theory of literature, and exposed in works such as Plato's Republic and Aristotle's Poetics, which are used as a basic theoretical source for this research. The two poems cited occupy, and this is one of their main marks, prominent positions in the didactic tradition of ancient literature, with Works and Days being the founding work of this genre, responsible for establishing its form, and the Lucretian poem its great renewing concerning its poetic conformation, a fact that justifies the choice of the texts for the present study. It is also necessary to remember the need for new studies aiming at understanding didactic poetry, especially in Brazil, largely because of the still scarce critical bibliography available on this subject. Thus, in the first part of this research, We investigated the main issues surrounding the didactic genre, from the point of view of modern aesthetics to that of the classical theory of literature, established in Greco-Latin antiquity, to reveal the problems and contradictions that mark this genre, so that, starting from the reading of the individual works, it will lead us at a more exact interpretation of the meaning and characteristics of this genre, even if anchored in the ancient theory of mimesis. And that was also the objective of our second chapter, in which we analyze the hesiodic poem according to its alleged mimetic configuration, which it is intended to present, establishing from this the most relevant characteristics and differences that distinguish didactic poetry from other literary genres of the antiquity, like the epic, for example. Therefore, in the third chapter, we will develop the same study about the mimetic configurations of didactic poetry, only with the lucretian poem in mind, to present the reasons that lead us to believe in such a poem as a watershed of this tradition, due to the structural innovations presented in it.